Is the Islam in Islamophobia the Same as the Islam in Anti-Islam; or, When Is It Islamophobia Time? - AbdoolKarim Vakil (e-cadernos ces)
Through an exercise of discourse genealogy, this paper addresses the concept of Islamophobia as far as the users and object of the concept concerns. By analysing the different political contexts in which Islamophobia has appeared and has been used in Britain and elsewhere, I argue that it is a politically powerful concept for the structuring and strengthening of Islamic subjectivities in Europe, namely because it is a concept with its origins in an Islamic perspective. Rather than what it intends to denounce – a new, more or less obvious hate for Muslims – it shows the construction and affirmation of a Muslim political subjectivity in Europe.